Rendering life molecular models, modelers, and excitable matter - Myers, Natasha 1974- (Experimental futures : technological lives, scientific arts, anthropological voices, 2015)
Crystallographic renderings -- Tangible media -- Molecular embodiments -- Rending representation -- Remodeling objectivity -- Machinic life -- Lively machines -- Molecular calisthenics -- Conclusion: what is life becoming? -- Appendix: a protein primer